Reimagining textuality: digital convergence and literary adaptation in Indonesia - Moh Atikurrahman (Lingua Technica: Journal of Digital Literary Studies, 2025)
Background: This article explores the multimodal circulation of Indonesian literary texts through television and digital adaptations, focusing on their implications for the conceptualization and cultural valuation of literature in the digital age. Objective: The technological boom and evolving reading practices have shaped how literature is disseminated, especially through intersemiotic media platforms. Method: Drawing on theories of cyberculture and media convergence (David Bell dan Tim Dwyer), this study analyzes examples such as the adaptation of Laskar Pelangi by Andrea Hirata into film and television, Bumi Manusia by Pramoedya Ananta Toer into cinema, and Tenggelamnya Kapal Van Der Wijck by Hamka into both screen and digital fandoms. Results: These cases reveal a cultural ecosystem in which television, internet platforms, and user-generated content converge to sustain literary texts and cultivate new modes of engagement. Implication: The role of the intellectual is not to mourn the “loss” of traditional literary values, but to explore the new affordances of digital storytelling, critical fandom, and narrative remixing as legitimate—and increasingly influential—modes of cultural expression. Novelty: The shift from print-centered authority to interactive and collaborative reinterpretation challenges traditional notions of originality and authorship while expanding access to literature across social strata.